Organic nanoparticles with ultrahigh stimulated emission depletion efficiency for low-power STED nanoscopy. Issue 27 (2nd July 2019) - Man, Zhongwei; Lv, Zheng; Xu, Zhenzhen; Cui, Hongtu; Liao, Qing; Zheng, Lemin; Jin, Xue; He, Qihua; Fu, Hongbing
Abstract : We prepared a STED probe with ultrahigh stimulated emission depletion efficiency for low-power STED nanoscopy. Abstract : Stimulated emission depletion (STED) nanoscopy is a powerful sub-diffraction imaging tool to probe subcellular structures and organelles. Conventional organic dyes require high STED power ( P STED ) to obtain sub-diffraction resolution, leading to serious photo-bleaching. Herein, this study demonstrates highly emissive silica-coated core–shell organic nanoparticles (CSONPs) as a new type of photostable probe with ultrahigh stimulated emission depletion efficiency for low-power super-resolution STED nanoscopy. The CSONPs offer (i) efficient red emission with high solid-state fluorescence quantum yields around 0.6, (ii) large Stokes shift of 150 nm and (iii) high photostability owing to silica shell protection. The stimulated emission depletion efficiency ( η ) of CSONPs was extremely high up to η = 99% (the highest value reported so far) with a saturation intensity as low as I sat = 0.18 MW cm −2 . Moreover, this research demonstrates the super-resolution imaging of living HeLa cells stained using CSONPs with a lateral spatial resolution of 63 nm at an extremely low depletion power of I STED = 0.89 MW cm −2 and a long-term stability >600 s at η = 80% without obvious fatigue. The excellent and comprehensive performances of the CSONPs are promising for super-resolution imaging in biological applications.